1985
DOI: 10.1021/np50039a034
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Indian Rutaceae. Chemical Investigation of Limonia alata and Evodia lunu-ankenda

Abstract: As part of our systematic chemical investigation of some of the members of the Rutaceae which are used in folk medicine, we report the isolation of several natural compounds from Limonia alata W. & A. (1) and Evodia lunu-ankenda Merr. (1).The petroleum ether extract of the bark of L. alata furnished the pyranocoumarins, xanthyletin (2) and xanthoxyletin (2), and the triterpene lupeol (3). From the fruits of the same species the pyranocoumarin, seselin (4), was isolated.Examination of the basic fraction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The remaining two doublets at δ 7.05 (J ) 3.0 Hz) and δ 7.56 (J ) 3.0 Hz) were coupled to each other. These substitution patterns, combined with the fact that furoquinolines have been found in other Rutaceae, 12 strongly suggested the presence of a furoquinoline skeleton. Indeed, these aromatic proton resonances matched very well those of dictamnine.…”
Section: Resultsmentioning
confidence: 90%
“…The remaining two doublets at δ 7.05 (J ) 3.0 Hz) and δ 7.56 (J ) 3.0 Hz) were coupled to each other. These substitution patterns, combined with the fact that furoquinolines have been found in other Rutaceae, 12 strongly suggested the presence of a furoquinoline skeleton. Indeed, these aromatic proton resonances matched very well those of dictamnine.…”
Section: Resultsmentioning
confidence: 90%
“…Plants of the genus Ruta have been commonly used in both ancient and modern medicine practices in the Mediterranean region to cure pulmonary diseases, rheumatic diseases and helminthic infections [15,27]. A large number of chemical constituents have been isolated from the genus Ruta, such as coumarins, alkaloids, benzoquinones, flavone glycosides, sterols, triterpenoids, acridone alkaloids, stigmasterol, lupeol, 5-methoxyarborinine, 5-hydroxyarborinine, ostruthin, bergapten, psoralen, xanthotoxin, limonoid obacunone, isopimpinellin, integriquinolone, kokusaginine, dictamnine, furoquinolin alkaloid, xanthyletin and xanthoxyletin [28,29]. It was also reported that coumarin compounds are the major constituents of the plants in the Rutaceae family, with about two hundred different coumarins being identified [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Leptonol demonstrated good antipyretic and antioxidant activities, while both chromenes showed moderate analgesic and anti-inflammatory activities, rationalizing the use of M. lunu-ankenda in treating conditions such as fever and inflammation in folklore practices [ 8 ]. Furoquinoline alkaloids, dictamnine, evolitrine, kokusaginine, and N -methyl-4-methoxy-2-quinolone, along with marmesin, were also successfully isolated from the basic fraction of bark extract [ 25 ]. Furthermore, dictamnine (4-methoxyfuro[2,3-b]quinoline) and evolitrine (4,7-dimethoxyfuro[2,3- b ]quinoline), which were isolated from the bark of M. lunu-ankenda , were reported to have moderate antifeedant activity [ 26 ].…”
Section: Phytochemical Compounds Isolated From Melicope mentioning
confidence: 99%